PENINGKATAN KEMAMPUAN PEMILIHAN KARIR MELALUI MODEL LAYANAN INFORMASI BERBASIS WHATSAPP GROUP DI SEKOLAH - MAE ENDANG IRIASTUTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The ability to choose a career is an individual's ability to complete career development tasks, which are in accordance with the stage of development. The discussion about the ability to choose a career is motivated by the problem, there are still many students who are confused in determining their career after graduating from SMK. During the current Covid-19 pandemic, online consultation is an alternative. The tendency of students today to prefer online social media while WhatsApp is the most popular application. This counseling guidance action research aims to determine the improvement of career choice skills through WhatsApp Group-based information services for class XII students of SMK Negeri 1 Kalasan for the 2020-2021 school year. Determination of the sample using simple random sampling technique. The research subjects were 31 students. Research design using Kemmis and McTaggart models with 4 stages. The results showed that the score of the ability to choose a career and use WhatsApp Group in the first cycle obtained a total score of 129.25 with an average of 83.39%, while in the second cycle the total score was 135.2 with an average of 87.25%. an increase of 3.86%. This can also be proven to students that their motivation increases, they have a positive self-concept, their understanding of higher education and the world of work increases which makes their ability to choose careers increase. So that this research can be concluded that the hypothesis is accepted, namely an increase in career decision-making abilities through WhatsApp Group-based information services for students of SMK Negeri 1 Kalasan for the academic year 2020-2021. ABSTRAKKemampuan pemilihan karir merupakan kemampuan individu dalam menyelesaikan tugas perkembangan karir, yang sesuai dengan tahap perkembangannya. Pembahasan tentang kemampuan pemilihan karir dilatarbelakangi oleh masalah, masih banyaknya peserta didik yang bingung dalam menentukan karirnya setelah lulus SMK. Pada masa pandemic Covid-19 seperti saat ini, konsultasi daring adalah salah satu alternative. Kecenderungan peserta didik saat ini lebih menyukai media sosial secara online sedangkan WhatsApp adalah aplikasi yang paling popular. Penelitian tindakan bimbingan konseling ini bertujuan guna mengetahui peningkatkan kemampuan pemilihan karir melalui layanan informasi berbasis WhatsApp Group untuk siswa kelas XII SMK Negeri 1 Kalasan tahun pelajaran 2020-2021. Penentuan sampel menggunakan teknik simple random sampling. Subjek penelitian berjumlah 31 peserta didik. Desain penelitian dengan model Kemmis dan McTaggart dengan 4 tahapan. Hasil penelitian menunjukkan bahwa skor kemampuan pemilihan karir dan pemanfaatan WhatsApp Group pada siklus I didapat jumlah skor 129,25 dengan rata-rata 83,39%, sedangkan pada siklus II didapat jumlah skor 135,2 dengan rata-rata 87,25%, terdapat peningkatan sebesar 3,86%. Hal ini dapat dibuktikan juga pada peserta didik bahwa motivasinya meningkat, mempunyai konsep diri positif, pemahaman perguruan tinggi dan dunia kerja meningkat yang menjadikan kemampuan pemilihan karir meningkat. Sehingga penelitian ini dapat disimpulkan bahwa hipotesis diterima yakni adanya peningkatan kemampuan pengambilan keputusan karir melalui layanan informasi berbasis WhatsApp Group pada siswa SMK Negeri 1 Kalasan tahun pelajaran 2020-2021.